Climate change and future rice production in India : a cross country study of major rice growing states of India /: a cross country study of major rice growing states of India. (2019) - Palanisami, K; Kakumanu, Krishna Ry; Nagothu, Udaya Sekhar; Ranganathan, C. R
No abstract available